632. A Randomized, Placebo-Controlled, Double-Blind, Clinical Trial Evaluating Two Dose Regimens of Rifaximin (550mg daily or twice-daily) for Chemoprophylaxis Against Travelers' Diarrhea Among Deployed U.S. and U.K. Military Personnel (PREVENT TD). (31st December 2020) - Gutierrez, Ramiro L; Burns, Daniel; Lalani, Tahaniyat; Bennett-Carter, Denise; Fraser, Jamie; Riddle, Mark; Connor, Patrick; Porter, Chad; Troth, Thomas; Ruck, Richard; Barton, Jerry; Tilley, Drake H; et al.
Abstract: Background: Travelers' diarrhea (TD) is a leading threat to military readiness. Most trials of rifaximin chemoprophylaxis involve civilians or short-duration travel, whereas military travelers are exposed for longer periods at austere locations and are often physically taxed. We sought to assess efficacy of two regimens among military personnel deployed overseas. Methods: This was a multi-site, double-blind, placebo-controlled trial of deployed military, randomized to placebo, rifaximin 550 mg daily, or rifaximin 550 mg twice-daily, for up to 42 days (1:1:1; 6 randomizations/block). Diaries were reviewed with subjects on return. Primary endpoint was time to first unformed stool (TFUS) in a TD episode. Other endpoints were assessed by intention to treat (ITT) and subgroups included incidence of any loose stool, meeting criteria for TD, safety, efficacy, adherence and impact to activity endpoints. Results: 343 subjects were included in the ITT population. All UK travelers deployed to a single-site in Kenya; US travelers mostly deployed to various Asia-Pacific locations. Of 73 (21.2%) subjects reporting diarrhea, 42 (57.5%) met TD criteria. Among rifaximin-treated subjects, 15.9% (n=17) reported diarrhea in the twice-daily arm, 20.7% (n=25) in the daily arm, vs. 27.0% (n=31) of placebo recipients; p=.04 and 0.26 respectively. TD was reported by 10.3% (n=11) and 10.7% (n=13) in the daily and twice-daily arms, vs. 15.7% (n=18) among placebo recipients; p=0.24 vs. 0.26 respectively. Among UK personnel, a twice-daily regimen vs. placebo resulted in significantly fewer TD episodes (1.6% vs. 11.9%; p=0.03). Adverse events were similar between groups. Table 1: Demographics, endpoints, and adverse events (Comparisons are across placebo vs. each dosing regimen. Intent-to-treat [ITT] population defined as subjects enrolled into the study, randomized, travelled and had follow-up. p-values calculated from chi-square or Fisher's exact test [categorical variables] and Wilcoxon-Mann-Whitney test [continuous variables]. Analyses performed on SAS v9.4. BID: twice-daily) Conclusion: This is the first trial comparing two high-dose regimens of rifaximin prophylaxis in deployed personnel. Unlike prior reports, neither regimen was associated with an overall significant decrease in TD, potentially due to low overall TD incidence. However, the twice-daily regimen was associated with a numerically lower incidence of diarrheal stool, and in the UK subject group, there was a significant decrease of both TD and diarrheal stool. The impact of variability in regional TD risk, pathogen distribution and adherence in austere deployment environments on efficacy will be reviewed. Disclosures: All Authors : No reported disclosures